Development of state social insurance in Ukraine - Сидорчук, Анатолій Андрійович (My University, 2018)
The article discusses the theoretical aspects of the development of state social insurance in Ukraine. In the course of research, analysis and synthesis as methods of theoretical knowledge of phenomena are used. Comparisons are used as empirical methods for the conducted research. For conducting research and substantiation of the relevant conclusions, theoretical models of state social insurance are analyzed, their general signs and differences are presented. Results of the research showed that Ukraine is trying to build financial support for the social protection system on the basis of the guaranteed minimum income of the population. The formation of the social insurance system in Ukraine is accompanied by the transition from Beveridge's model to the continental model of the European countries. Study of economic indicators that will accompany the transition by Ukraine to the continental model of social protection of the population opens up prospects for future research in this area of financial science.
Keywords: state; state social insurance